Drug-eluting balloons in coronary interventions: the quiet revolution?. (3rd July 2017) - Alfonso, Fernando; García-Guimaraes, Marcos; Navarrete, Gonzalo; Cuesta, Javier; Bastante, Teresa; Benedicto, Amparo; Rivero, Fernando; Cortese, Bernardo
ABSTRACT: Introduction : Drug-eluting balloons (DEB) may be considered as a 'quiet revolution' in percutaneous coronary interventions. Early-generation DEB eluting paclitaxel proved to be very effective in animal models to reduce neointimal hyperplasia. Areas covered : Review of DEB efficacy in patients with coronary de novo lesions and in-stent restenosis (ISR). Expert opinion : Many randomized clinical trials and meta-analyses have demonstrated the value of DEB in patients with ISR. In this setting, DEB are safe and effective with clinical and angiographic results superior to plain balloon angioplasty and at least equivalent to first generation drug-eluting stents (DES). In selected 'de novo ' lesions (bifurcation lesions, small vessels, diffuse disease, myocardial infarction) DEB represent an attractive alternative although additional evidence in these 'niche' indications is still required before a widespread clinical utilization can be recommended. Recently, new generation DEB have become available, offering interesting new possibilities (paclitaxel and also sirolimus) for coronary interventions. Further studies are required to compare the results of novel generation DEB with those of second-generation DES.